Geology of the Kansas Flint Hills: Ancient Ice Ages, Sea Levels, and Climate Change - Miller, Keith B. (My University, 2016)
During the Wolfcampian the mid-continent of North American lay within the low relief interior of the supercontinent Pangea in near equatorial latitudes. Throughout the Permian and into the Triassic this landmass drifted slowly to the north into higher latitudes (Rowley et al., 1985; Scotese, 1986; Witzke, 1990). In the Wolfcampian, the study area would have been relatively far from areas of active tectonism. The highlands of the ancestral Rockies lay ~500 km to the west and the Ouachita and Wichita uplifts were an approximately equal distance to the south. A broad low lying cratonic area probably lay to the north and east. The carbonate and fine clastic facies of the Council Grove and Chase Groups in northeastern Kansas suggest a vast shallow marine to marginal marine shelf periodically exposed during relative sealevel lowstands.
Citation: Miller, K. B. (2011). Geology of the Kansas Flint Hills: Ancient Ice Ages, Sea Levels, and Climate Change. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Geology; Flint Hills, Kansas; Ice Age; Sea Levels; Climate Change